2020
DOI: 10.1186/s12884-020-03223-0
|View full text |Cite
|
Sign up to set email alerts
|

Can people-centered community-oriented interventions improve skilled birth attendance? Evidence from a quasi-experimental study in rural communities of Cambodia, Kenya, and Zambia

Abstract: Background: Skilled attendance at delivery is a key marker for reducing maternal mortality. Effective community engagement strategies complemented by community health worker (CHW) services can improve access to maternal health services in areas with limited health infrastructure or workforce. Methods: A quasi-experimental study with matched comparison groups was conducted in Cambodia, Kenya and Zambia to determine the effect of integrated community investments on skilled birth attendance (SBA). In each country… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
1
7
0
1
Order By: Relevance
“…This may be attributed to the fact that regular contact with health workers during ANC, accords more opportunities for education and counselling about the need to seek for health care services during and after pregnancy [ 28 , 31 , 38 ]. Mothers who had at least one visit by a health field worker had higher odds of PNC utilisation, a finding similar to that of other studies done in similar contexts [ 39 , 40 ]. The repeated contact with health workers during pregnancy through ANC services and visits by health field workers promote confidence and familiarity with the health system leading to increased trust in the health system [ 36 ].…”
Section: Discussionsupporting
confidence: 88%
“…This may be attributed to the fact that regular contact with health workers during ANC, accords more opportunities for education and counselling about the need to seek for health care services during and after pregnancy [ 28 , 31 , 38 ]. Mothers who had at least one visit by a health field worker had higher odds of PNC utilisation, a finding similar to that of other studies done in similar contexts [ 39 , 40 ]. The repeated contact with health workers during pregnancy through ANC services and visits by health field workers promote confidence and familiarity with the health system leading to increased trust in the health system [ 36 ].…”
Section: Discussionsupporting
confidence: 88%
“…In addition to their roles of providing basic primary health care services, CHAs ensure increased modern contraceptive utilization through health promotion and behavioral change sessions and providing basic reproductive, maternal and newborn health (RMNH) interventions were including contraceptive counselling and administration of injectable contraceptives within the communities [ 46 , 48 ]. Being visited by field health workers has been shown to be associated with increased utilization of SRH services in several other studies [ 12 , 50 52 ].…”
Section: Discussionmentioning
confidence: 96%
“…The presence of a skilled health professional, such as a doctor, nurse or midwife who is trained to manage pregnancies, childbirth and the immediate postnatal period is one of the central elements in reducing maternal and child deaths [8][9][10]. Previous studies have shown that socioeconomic, cultural and other related factors influence SBA utilisation [11][12][13][14]. In addition, cultural and institutional norms like maleheaded households and gender-based power inequalities, through gender-based violence adversely affect women's sexual and reproductive health [15,16].…”
Section: Introductionmentioning
confidence: 99%